1987
DOI: 10.1002/ar.1092190108
|View full text |Cite
|
Sign up to set email alerts
|

Significance of increase in glucose 6‐phosphatase activity in brown adipose cells of cold‐exposed and starved mice

Abstract: Cytochemical and biochemical glucose 6-phosphatase (G6Pase) activity was examined in brown adipose tissues of normal, cold-exposed, or starved mice. In addition, G6Pase activity in white adipose tissue and hexokinase activity in brown and white adipose tissues were biochemically measured. In normal animals, the reaction product for G6Pase activity was localized in the endoplasmic reticulum and nuclear envelope of brown adipose cells. The amount of the reaction product increased in cold-exposed or starved anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…We concluded that the simultaneous increase in the two enzyme activities in the tissues of cold-exposed animals is probably related to "thermogenesis by substrate (futile) cycle between G6P and glucose" (Watanabe et al, 1987). As revealed in the present study, the increase in the two enzyme activities by cold-exposure was inhibited by sectioning of nerve fibers distributed to brown adipose tissues.…”
Section: Discussionsupporting
confidence: 66%
“…We concluded that the simultaneous increase in the two enzyme activities in the tissues of cold-exposed animals is probably related to "thermogenesis by substrate (futile) cycle between G6P and glucose" (Watanabe et al, 1987). As revealed in the present study, the increase in the two enzyme activities by cold-exposure was inhibited by sectioning of nerve fibers distributed to brown adipose tissues.…”
Section: Discussionsupporting
confidence: 66%
“…ductus epididymis (280) (19), seminal vesicle (270) (18). and brown adipose tissue (259.7) (43). The high G6Pase activity in these organs is related to glucose (or fructose) release into the blood, aqueous humor, epididymal fluid, or seminal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In rats exposed to low temperatures, HK activity was 1.15-and 1.17-fold higher in cardiac and gastrocnemius muscles respectively [51]. The exception in mammals was observed in the thermogenic brown adipose tissue of mice, where the increase in HK activity was between 1.9-and 2.5-fold [52,53].…”
Section: Introductionmentioning
confidence: 94%